EFEKTIVITAS MEDIA VIDEO TUTORIAL DALAM MENINGKATKAN KETERAMPILAN VOKASIONAL MEMBUAT DOMPET MAKRAME BAGI ANAK TUNARUNGU - Ibrahim, Muhammad; Fatmawati, Fatmawati (Jurnal Penelitian Pendidikan Khusus, 2022)
This research was conducted by the author at SLB N 2 Padang. This study discusses learning fashion, which only focuses on learning to sew, which has not been taught much innovation. Based on these problems, the author tries to teach making different types of clothing and different teaching methods, namely making macrame wallets. This study uses experimental research methods in the form of pre-experimental design with one group pretest-posttest type. And the data obtained were processed and compared using the Wilcoxon Rank Test. The results of this study are the pretest and posttest values can be seen Z count = -2.041b with probability or Asymp Sig (2-tailed) = 0.041. In the Wilcoxon test table, the critical value at the error level ( ) is 0.05. Then it is found that the calculated probability Z is less than the specified probability (0.041 < 0.05). Therefore Ha is accepted and H0 is rejected. Thus, it can be concluded that the video tutorial media is effective in improving the vocational skills of making macrame wallets for deaf children.